Case Report: mTOR inhibitor treatment for epithelioid angiomyolipoma harboring biallelic TSC2 mutations - Ishikawa, Shiori; Ouchi, Kota; Wakayama, Shonosuke; Kasahara, Yuki; Komine, Keigo; Imai, Hiroo; Saijo, Ken; Yamazaki, Yuto; Takahashi, Masanobu; Shirota, Hidekazu; Kawakami, Hisato (Frontiers in Oncology, 2026)
IntroductionAngiomyolipoma (AML) is a mesenchymal tumor composed of blood vessels, smooth muscle, and adipose tissue, and is generally considered benign. However, epithelioid angiomyolipoma (eAML) is a rare and aggressive variant with metastatic potential. Molecular characterization utilizing the tuberous sclerosis complex (TSC)–mTOR pathway is beneficial in advanced disease. This report describes the clinical course, histopathological findings, and molecular analysis of a patient with metastatic eAML.MethodsA 59-year-old Japanese man with no personal or family history of tuberous sclerosis (TSC) was admitted to the hospital with gradually worsening back pain and initially diagnosed with clear cell renal cell carcinoma (ccRCC). He underwent nephrectomy, followed by hepatic recurrence treated with pazopanib and subsequent axitinib. Both were discontinued due to intolerance, and the two remaining liver metastases were surgically resected. Histopathological examination of the resected lesions revealed eAML. After several recurrences and resections, unresectable hepatic and pulmonary metastases eventually developed.ResultsComprehensive genomic profiling (CGP) using the resected liver metastasis specimen identified two somatic TSC2 mutations: a frameshift mutation (p. P677fs*21; variant allele frequency [VAF] 0.0789) and a nonsense mutation (p. S1469*; VAF 0.0736), suggesting biallelic loss of TSC2. Based on these findings, everolimus, a mammalian/mechanistic target of rapamycin (mTOR) inhibitor, was recommended, which markedly reduced the size of the metastatic lesions and was continued for 24 months until disease progression without severe adverse events.DiscussionThis case suggests that CGP can help identify actionable alterations in eAML, such as TSC2 mutations, to guide personalized therapy with mTOR inhibitors.